Re-thinking Physical Activity Programs for Older Brazilians and the Role of Public Health Centers: A Randomized Controlled Trial Using the RE-AIM Model - Tânia Rosane Bertoldo Benedetti; Cassiano Ricardo Rech; Lisandra Maria Konrad; Fabio Araujo Almeida; Fabiana A. Brito; Wojtek Chodzko-Zajko; Andiara Schwingel (Frontiers Media S.A., 2020)
Background: Explored the role of public health centers in the delivery of physical activity programs to older Brazilians.Methods: Total of 114 older adults (81% women) from public health centers across the city of Florianopolis, Brazil, were randomized into three groups: behavior change group (n = 36), traditional exercise group (n = 52), and control group (n = 26). The behavioral change group included 12 weekly meetings (2 h each). The traditional exercise group offered a 12-week exercise class. Individuals in the control group participated only in measurements. Program evaluation included a mixed-methods approach following the RE-AIM framework (reach, effectiveness, adoption, implementation, and maintenance). Trained interviewers conducted 12 focus groups and 32 interviews with participants in the program, professionals delivering the programs, community health workers, and local and city administrators overseeing public health centers. Participants completed health, quality of life, and fitness assessments at four time points.Results: The study reached 11.5% of the eligible population in the community. Older adults' resistance to change and limited understanding of behavior change science by public health center staff hindered program reach. Physician encouraging patient participation and personal invitations by community health workers were perceived as favorable factors. Results of program effectiveness and maintenance suggest that behavior change strategies may be better suited than traditional exercise classes for decreasing sedentary time and increasing moderate-to-vigorous physical activity, as well as improving participants' quality of life. Only 14% of public health centers in the city adopted the programs. Heavy workload of health educators delivering the programs and limited physical space for program delivery were barriers for adoption. The fidelity of program delivery was high and indicates that the programs are culturally-appropriate for the Brazilian context and feasible for implementation by local health educators.Conclusions: Our findings support the potential for dissemination of behavior change and traditional exercise programs to older adults through public health centers in Brazil.REBEC: RBR-9pkxn2 (retrospectively registered) Register April 20, 2019.